Diffusion Tensor Imaging Analysis of Tumefactive Giant Brain Lesions in Multiple Sclerosis. Issue 3 (24th January 2012) - Miron, Shmuel; Tal, Sigal; Achiron, Anat
Abstract : ABSTRACT: BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) quantifies the motion of water within brain tissue. Inflammation leads to tissue disruption, resulting in increased diffusivity and decreased directionality. We aimed to quantify the damage within tumefactive giant brain lesions (TGL) in multiple sclerosis (MS) using MRI and DTI methodology. METHODS: Region of interest were determined on TGL and acute MS lesions to obtain metrics such as volume, apparent diffusion coefficient (ADC), fractional anisotropy (FA), axial diffusivity (λ|| ), and radial diffusivity (λ⊥ ). RESULTS: We identified 10 TGL in 10 patients with MS. The incidence of TGL was 2.8%. Comparing TGL to acute 16 MS lesions, DTI metrics demonstrated significantly higher ADC, λ|| and λ⊥ diffusivities and lower FA values in TGL ( P <.001). Five TGL were reevaluated after 120 days by MRI and DTI metrics. Significant group changes were detected at 120 days: TGL volume decreased, ADC, λ|| and λ⊥ values were lower and FA was higher ( P < .01). CONCLUSIONS: Within the spectrum of acute MS lesions, TGL present DTI metrics of an intense acute inflammatory process. Analysis of TGL progression proposes that DTI metrics sensitively detects micro‐structural changes in TGL from acute inflammation towards lesion recovery and reorganization.